Surface Circulation off Kuala Terengganu in the Transitional Period between the Northeast and Southwest Monsoons - Saadon, Mohd Nasir; Marghany, Meged Mahmoud (Universiti Putra Malaysia Press, 1996)
The aim of this investigation is to understand the surface current circulation pattern off Kuala Terengganu. A drifting drogue was used to measure surface current during April 1993, the transitional period between the northeast and southwest monsoon seasons. Our results show that the drifting drogue moves in an almost circular motion, suggesting the presence of an eddy. However, further studies are needed to confirm the existence of an eddy off Kuala Terengganu during the transitional period.